On the Support of Solutions to a Two-Dimensional Nonlinear Wave Equation - Wenbin Zhang; Jiangbo Zhou; Lixin Tian; Sunil Kumar (Journal of Mathematics)
It is shown that if u is a sufficiently smooth solution to a two-dimensional nonlinear wave equation such that there exists L>0 with supp u(i)⊆[−L,L]×[−L,L], for i=0,1, then u≡0.